Cephalomedullary Nail Breakages in a Multicenter Insertion vs. Retrieval Database Comparison - Anton P. Lambers, MBBS, BMedSc(Hons), MS(Dist), DipMgt, FRACS(Orth), FAOrthA; Bertram Rieger, MD; Alan Kop, PhD, MSc, PGDip, BAppSc; Moreica B. Pabbruwe, BEng(Hons), PhD; Tom Briffa, PhD; Jessica Perring, BSc, MD, MS; Peter D'Alessandro, MBBS(Hons), FRACS(Orth), FAOrthA; Piers J. Yates, MBBS, BSc(Hons) MRCS(Eng), FRCS(Tr & Orth), FRACS(Orth), FAOrthA (JBJS Open Access)
Background:. Cephalomedullary nails are used for internal fixation of proximal femur fractures, pathological fractures, and for revision fixation in the case of failures. Nail breakages are rare, with published figures demonstrating a high variability with a previous benchmark set at less than 1.3%. The aim of this study was to use a large and geographically isolated patient cohort to better define and compare the proportion of implant breakages across a range of cephalomedullary nails. Methods:. Implantation data were collected from electronic theater records at all tertiary public orthopaedic hospitals in the state of Western Australia between 1 January, 2001, and 5 July, 2017, to capture a consecutive series of implant insertions across all indications. This was linked to Western Australia's Centre for Implant Technology and Retrieval Analysis (CITRA) nail repository records to identify broken nails received for analysis in the subsequent years until data collection ceased on 5 July, 2024. Results:. Three thousand eight hundred eighty-two cephalomedullary nails were implanted. There were 18 nail breakages in this cohort recovered by CITRA, giving an overall breakage proportion of 0.5%. While breakages were rare, the Trochanteric Fixation Nail-Advanced (TFNA) demonstrated a 7-fold higher proportion of reported breakages (6/393; 1.5%) compared with its predecessor the proximal femoral nail antirotation (PFNA; 6/2,621; 0.2%, p = 0.002). The proportions of reported breakages in the Gamma3 and PFN prostheses were 0.6% (2/320) and 0.7% (4/548), respectively. Conclusions:. In this large consecutive sample of cephalomedullary nail patients, the TFNA appears to have a higher proportion of reported breakages than one of its predecessors, the PFNA, and this sits outside our previously defined benchmark. Breakages need to be considered in conjunction with other causes of failure and the index diagnosis when making decisions about implant choice in the management of proximal femur fractures. Further studies that are better able to deal with the many confounding variables of implant fatigue failure are required. Level of Evidence:. Therapeutic Level III (Retrospective Cohort Study). See Instructions for Authors for a complete description of levels of evidence.